Design and Implementation of Beidou Differential Positioning Scheme for Train Control System - WANG Yeliu; BAI Changlong; XIAO Lizhi (Kongzhi Yu Xinxi Jishu)
Accurate locomotive position is a prerequisite for train operation control and the existing locomotive positioning technology has the problems such as poor positioning accuracy, high investment cost and maintenance difficulties. Based on the Beidou satellite differential positioning technology, this paper proposed a locomotive precise positioning scheme suitable for China train control system. It introduces the technical principle, design scheme and implementation scheme of the system in detail, describes the key technical difficulties of adopting Beidou satellite differential technology in railway environment, gives the corresponding solutions and test data. The specific application effects in the train control system of LKJ-15 show that it can enhance refined and intelligent control of the locomotive and improve operation efficiency of the railway system.